Red blood cell product utilization in patients undergoing allogeneic stem cell transplantation. Issue 7 (8th April 2019) - Gastecki, Karen; Shanley, Ryan; Welbig, Julie; Cohn, Claudia; Brunstein, Claudio G.
Abstract : BACKGROUND: The risk of transfusion reactions (TR) and the cost of blood has led to efforts to reduce blood use. We changed our practice to transfuse just one instead of two units of red blood cells (RBC) when hemoglobin ≤8 g/dL due to patient blood management (PBM) recommendations. METHODS AND MATERIALS: We compared RBC utilization in patients receiving allogeneic HCT in the 10 months before (control arm) and 13 months after implementation of this new practice (intervention arm). We used regression models to estimate the independent effect of transfusion practice, length of hospitalization, the conditioning regimen, and donor type for patients who received at least one RBC unit. The outcome variable was total number of inpatient transfusions. In addition, a survey assessed the impact of this. RESULTS: Cohorts were matched for age, primary diagnosis, graft source, and conditioning regimen. The median number of RBC units transfused/patient was identical in both arms (4; interquartile range 19 units/patient). Using the regression model, only length of stay (relative increase of 1.035 units/day; 95%CI, 1.0271.043) was an independent predictor of the number of RBC units a patient received. When data were normalized/1000 patient days, the control arm received 240 units vs the intervention arm, which received 193 units, resulting in a reduction of 47 units transfused/1000‐patient‐days, which was not statistically significant ( p ‐value = 0.32). The survey of RNs showed that it positively affected the workflow. CONCLUSIONS: There was a modest reduction in RBC utilization based on units transfused/1000‐patient‐days. There was a positive impact on RN workflow.